Peran Promotional Mix Dalam Membentuk Brand Image Produk City Car di Kota Pekanbaru (Studi Kasus pada Daihatsu Sirion) - Dita, Monika; Nursanti, Aida; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the role of promotional mix variables which consist of advertising, personal selling, sales promotion, public relations, and direct marketing towards brand image of Daihatsu Sirion car in Pekanbaru. Sample’s selection that used with the method of non-probability sampling. Selected sample is consumer who uses Daihatsu Sirion car specifically who lives in Pekanbaru city, ever been involved in Daihatsu Sirion promotional mix activity, and the consumer that considered mature enough (about 20 years old) to fill the questionnaire.The data analysis that used is multiple regression linear analysis which use SPSS version 20. The result indicates simultaneously that all variables of promotional mix have a role in make a brand image of Daihatsu Sirion car in Pekanbaru. Known partially that only sales promotion and direct marketing variables that has significant effect for brand image of Daihatsu Sirion car in Pekanbaru. Public relation variable also has the role in establish brand image of Daihatsu Sirion car in Pekanbaru, however it is not significant. Sales promotion is a kind of promotional mix variable that has the most dominant role on establish brand image of Daihatsu Sirion car in Pekanbaru.